General formalism for the stability of thin-shell wormholes in 2+1 dimensions - Bejarano, Cecilia Soledad (2014)
In this article we theoretically construct circular thin-shell wormholes in a 2+12+1 -dimensional spacetime. The construction is symmetric with respect to the throat. We present a general formalism for the study of the mechanical stability under perturbations preserving the circular symmetry of the configurations, adopting a linearized equation of state for the exotic matter at the throat. We apply the formalism to several examples.